Developing web based visual power system symmetrical short circuit tools using web based application - Mat Leh, Nor Adni (2008)
Fault studies form an important part of power system analysis. In power system, the problem of fault analysis consists of determining the current and bus voltages. It is also used in designing the power system protection. Thus, due to its important in power system, this project has been brought to develop an accessible fault analysis tools. Web based application and PHP language was used in order to build the fault analysis tools. Component web based is a reusable program and it is easy to maintain. The user can easily access the web wherever they want as long as the internet services is available. This service is more alike to be friendly with the users since the users can access the services without the limiting time. In this project, the program will developed by using PHP language. PHP language is open source and its code is simple and straight forward.